PENGARUH GOVERNMENT SIZE, LEGISLATIVE SIZE, DAN CAPITAL EXPENDITURE TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN OPINI AUDIT SEBAGAI VARIABEL MODERASI - Dafina Melfiana Fanni (2022)
This research is a quantitative study which aims to determine the effect of legislative size, government size and capital expenditure on the level of disclosure of LKPD with a moderating variable. The sample is 485 LKPD from all over Indonesia which have been audited for the 2020 period with the option of purposive sampling. The analysis technique used is path analysis using Smart PLS 3 software with a significance level of 5%. The results of the test show that (1) Legislative size has no effect on the level of LKPD disclosure (2) Government Size has an effect on the level of disclosure on LKPD (3) Capital Expenditure has an effect on the level of disclosure on LKPD (4) Audit opinion cannot moderate the effect of legislative size on the level of disclosure LKPD (5) Audit opinion moderates the influence of government size on the level of disclosure of LKPD (6) Audit opinion cannot moderate the effect of capital expenditure on the level of disclosure of LKPD.